The use and improvement of karst grassland - Anton VIDRIH; Franc LOBNIK (Acta Agriculturae Slovenica)
The Slovenian Karst Plateau is presented in the article and reviewed are the possibilities for the development of sustainable grassland utilisation with livestock grazing. This can have positive impact on the biodiversity of the region and on well kept appearance of the landscape. Limestone and dolomite rocks form karstic character of land, which is expressed through geomorphological, hydrographical as well as floristic and vegetational, soil, agricultural, and settlement pattern. The key indicator for a land stability and productivity is succession. It is the process of change and development in entire communities; soil, micro-organisms, animals and plant life. To understand the nature of the forces that influence individual plants within the Karst pasture sward, we need to consider what happens in the sward from the plant's point of view. To maintain karst grassland and prevent it from bush encroachment, the grazing of livestock is of vital importance. Grazing livestock greatly affects the composition of pasture plant communities. With proper grazing management animals always cause pasture to be a more complex mixture of plants than it otherwise would be. This is because animals graze selectively and in patches, and the effects vary in time and space. They do collect the nutrients from wider area and return them more concentrated to the soil. This has great influence on site fertility and vitality of the ecosystem. All this has an effect on sward development, which contains a wide variety of plants adapted enough to survive their different local conditions. It is quite logical that throughout the process of evolution, the pasture plants and animals have adapted to each other and that grazing is not harmful to those plants.